2013
DOI: 10.1021/am4004446
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectra, and Electron-Transfer Reaction of Aspartic Acid-Functionalized Water-Soluble Perylene Bisimide in Aqueous Solution

Abstract: An aspartic acid-functionalized water-soluble perylene bisimide, N,N'-di(2-succinic acid)-perylene-3,4,9,10-tetracarboxylic bisimide (PASP) was synthesized and characterized. It has absorbance maximum A(0-0) and A(0-1) at 527 and 498 nm (ε ≈ 1.7 × 10(4) L cm(-1) mol(-1)) respectively in pH 7.20 HEPES buffer. Two quasi-reversible redox processes with E1/2 at -0.17 and -0.71 V (vs Ag/AgCl) respectively in pH 7-12.5 aqueous solutions. PASP can react with Na2S in pure aqueous solution to form monoanion radical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 56 publications
(95 reference statements)
9
37
0
Order By: Relevance
“…[55,71] The aggregation stabilizes the radical anion species, which is also observed in PDI aggregation in solution and films. [72,73] Upon the immersion of the greenish FTO|TiO 2 |BPTICNP-2 electrode in Na 2 S 2 O 4 -free air-saturated phosphate buffer solution (pH 8.0, 0.1 m ), the greenish electrode gradually turned yellow. The color change indicates that the BPTICNP-2 radical anion is oxidized slowly by the oxygen dissolved in water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[55,71] The aggregation stabilizes the radical anion species, which is also observed in PDI aggregation in solution and films. [72,73] Upon the immersion of the greenish FTO|TiO 2 |BPTICNP-2 electrode in Na 2 S 2 O 4 -free air-saturated phosphate buffer solution (pH 8.0, 0.1 m ), the greenish electrode gradually turned yellow. The color change indicates that the BPTICNP-2 radical anion is oxidized slowly by the oxygen dissolved in water.…”
Section: Resultsmentioning
confidence: 99%
“…[55,71] The aggregation stabilizes the radicala nion species, which is also observed in PDI aggregation in solutiona nd films. [72,73] Upon the immersion of the greenish FTO j TiO 2 j BPTICNP-2 electrode in Na 2 S 2 O 4 -free air-saturatedp hosphate buffers olution (pH 8.0, 0.1 m), the greenish electrode gradually turned yellow.T he color change indicates that the BPTICNP-2 radicala nion is oxidized slowly by the oxygen dissolved in water.The oxidation reaction was followed as af unction of time by absorption spectroscopy,w hich shows as mooth conversion to the initial absorption spectrum of the neutrals pecies ( Figure S3). Importantly,t he observed lifetime of the BPTICNP-2 radical anion is severalt ens of seconds (halflife t 1/2 = 39 s).…”
Section: Electrochemical Studiesmentioning
confidence: 99%
“…The versatility of PBIs comes from their ability to be reduced to form a radical anion, and then further reduced to the dianion . These reduced states result in a change in color and sometimes make the material conductive . For sensors, this radical anion can be induced or reduced depending on the molecule it is detecting.…”
Section: Figurementioning
confidence: 99%
“…Zang and co‐workers reported that the PBIs are reduced to radical anions by hydrazine in DMF; Marcon and Brochsztain also reported the generation of PBI radical anions in water/ethanol using Na 2 S 2 O 4 . Our previous work has demonstrated that Na 2 S can reduce an aspartic‐acid‐functionalized PBI dye in aqueous solution . The formation of long‐lived charge‐separated states with the addition of Mg(ClO 4 ) 2 to a benzonitrile solution of zinc–phthalocyanine–PBI pentameric arrays has been reported .…”
Section: Introductionmentioning
confidence: 98%